Early Detection and Intervention of Preschool-Aged Children Using Android-Based Monitoring during the COVID-19 Pandemic in Central Java - Triwiji Lestari; Elisa (Jurnal Keperawatan Indonesia)
Preschool age is widely recognized as a critical phase in child development, often referred to as the golden period, the window of opportunity, and the critical period. Alarming statistics from the Indonesian Ministry of Health reveal that 16% of Indonesian toddlers, amounting to 0.4 million children, experience developmental delays, encompassing fine and gross motor skills, hearing impairments, reduced cognitive abilities, and speech delays. This study aims to assess the effectiveness of an Android-based early detection and intervention system on the development of preschool children during the challenging circumstances of the COVID-19 pandemic in Central Java. The research employed a quasi-experimental design without a control group using a range of instruments, including observation sheets, the Sahabat Bunda application, the pre-screening developmental questionnaire (PDQ), and anthropometric measurements. Data analysis was conducted using the Wilcoxon test because the data were not normally distributed. The study’s results underscore a significant influence between the initial developmental status of children and their subsequent progress following developmental intervention, with a remarkable p-value of 0.001. In conclusion, this research demonstrates that providing developmental intervention positively impacts the overall development of preschool children. This study substantially benefits the community, specifically preschool-age children and their parents. The utilization of the Sahabat Bunda application emerges as a valuable tool for early detection of developmental issues and to foster the growth of preschool-age children. This research contributes to enhancing child development, particularly in the context of the COVID-19 pandemic.